Teaching Nazi Culture - Parmalee, Patty Lee (Radical Teacher, 2014)
Nazi Culture would seem at first to be a very esoteric subject to teach to the rather practical-minded and not very cosmopolitan students of a northern New Jersey state college. But of course it is really a distancing technique, a Verfremdungseffekt a la Brecht. Teaching fascism is not really teaching fascism per se, but an angle for teaching capitalism and socialism. And teaching Nazi culture is an angle for teaching some of the purposes of capitalist ideology.